Improving HPV-related health literacy in the Austrian population – A participatory research approach - Magdalena Meikl; Tanja Karl; Anja Schuster; Gertie Janneke Oostingh (Human Vaccines & Immunotherapeutics)
Human papilloma virus (HPV) infections are widespread and affect a main part of the population. Long-term risks of such infections include the development of HPV-induced cancers. Although available, preventive measures are not utilized by the Austrian population to their fullest extent. Only 40% of all Austrians have completed the vaccination programme and only 46% are aware of HPV. This may be attributed to a lack of awareness or an ineffective approach in disseminating information to raise awareness about this health issue. Our aim was to determine which knowledge on HPV infections and vaccinations is present in the Austrian population and to identify the preferred mode of communication for receiving information on health-related issues, including HPV. This objective was implemented in the context of a participatory research project together with citizen scientists, whereby a target group-oriented survey was developed. Data from 889 survey participants, analyzed with descriptive statistics, demonstrated significant gender- and age-related differences in HPV knowledge and information-seeking behavior. Men and individuals under 18 were significantly less informed, especially regarding transmission routes and HPV-related diseases. Women were more aware of the vaccine’s benefits and have higher vaccination rates. The use of clear, concise content and personal stories can foster engagement and address misperceptions. Customized HPV awareness campaigns and an integration of HPV education into school curricula should be implemented to facilitate early knowledge acquisition and vaccination uptake.